The Creation Music of E-san Fusion Calabrone - Sriwieng, Yuttapong; Sangsawang, Techadon; Namsanga, Pariyat; Pantasri, Pittayawat (Chophayom Journal, 2024)
This current study aims 1) to create a composition called "E-san Fusion Calabrone" and to 2) to study the concepts and inspirations behind the creation of the E-san Fusion Calabrone musical composition, a study was conducted by collecting information from documents, books, treatises, publications, relevant research studies, and interviews with two experts. The research findings reveal that. The creation of the composition "E-san Fusion Calabrone" involves the following steps. 1) In terms of musical form, a ternary form, where each section conveys different meanings based on the context of the melody was used. 2) For scale, the composition was created using the A natural scale. 3) In terms of tempo and rhythm, the tempo was set at 80 bpm and 100 bpm, with a drum set controlling the rhythm. 4) In terms of melody, the traditional Isan folk melody "Lai Maeng Phu Tom Dok" was applied by modifying, Augmentation, Diminution, and rearranging the notes, as well as incorporating improvisation. The concepts and inspirations behind the creation process include: 1) applying chord progression principles and Western music theory to rearrange into a fusion music style and creating melodies based on "Lai Maeng Phu Tom Dok" using a mix of Isan and Western instruments and 2) stemming from a familiarity with Isan folk melodies since childhood, recognizing the distinctive nature of Isan music that reflects the lifestyle, social conditions, and geography of various areas. The potential of Isan folk melodies to develop into a global level is evident, leading to the blending of "Lai Maeng Phu Tom Dok" with globally popular fusion music, using Western musical techniques with Isan folk melodies. Keywords: The Creation music, Isan folk music, Fusion music